2023
DOI: 10.7759/cureus.41071
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy of Direct Oral Anticoagulants and Low-Molecular-Weight Heparin in Cancer-Associated Thromboembolism: A Systematic Review and Meta-Analysis

Abstract: Patients diagnosed with cancer often experience an abnormal occurrence of venous thromboembolism (VTE) and its related complications. In order to evaluate the safety and effectiveness of both treatment approaches, we conducted a comprehensive systematic review and meta-analysis within the realm of cancer-associated thromboembolism. A thorough search was conducted across PubMed, the Cochrane Library, and Embase databases to find studies comparing direct oral anticoagulants (DOACs) with low molecular weight hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Macrophages present in these sites secrete inflammatory mediators, which sustain a condition of persistent low-level inflammation. The defective adipocytes lead to the generation of FFAs, which worsens inflammation and insulin resistance in nearby tissues [10].…”
Section: Inflammation and Its Role In Insulin Resistancementioning
confidence: 99%
See 3 more Smart Citations
“…Macrophages present in these sites secrete inflammatory mediators, which sustain a condition of persistent low-level inflammation. The defective adipocytes lead to the generation of FFAs, which worsens inflammation and insulin resistance in nearby tissues [10].…”
Section: Inflammation and Its Role In Insulin Resistancementioning
confidence: 99%
“…Hyperinsulinemia, a reaction to insulin resistance, increases the synthesis of molecules that promote the development of atherosclerosis, such as endothelin-1 and plasminogen activator inhibitor-1 (PAI-1). These chemicals facilitate the occurrence of inflammation, oxidative stress, and the multiplication of vascular smooth muscle cells, which are crucial mechanisms in the formation of atherosclerotic lesions [10]. Furthermore, insulin resistance leads to dyslipidemia, characterized by increased triglyceride levels and decreased high-density lipoprotein cholesterol (HDL-C) levels.…”
Section: Role Of Insulin Resistance In Initiating and Promoting Ather...mentioning
confidence: 99%
See 2 more Smart Citations
“…In general, these studies have shown that DOACs could be a superior therapeutic option for managing cancer-associated thromboembolism compared to low-molecular-weight heparin. Despite these results, low-molecular-weight heparins, particularly enoxaparin, an anti-factor Xa, are still frequently used in Spain among patients with cancer [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%